The captivity of former young female combatants of colombian armed groups (2012)
The article analyzes the situations that girls and young women who have demobilized from the Colombian armed conflict face due to the fact that they are women in the context of a patriarchal culture. These young ex-combatants, after a process that took them from childhood to war to the return to civilian life, construct discourses and question power relations in their search for wellbeing. These women are imprisoned by their contradictory feelings with respect to their gender and this situation will condition their lives as long as their discourses regarding respect for their gender are not addressed and resignified. Social Work seeks to question those relations, address discourse that have been silenced, rebuild a feminine identity, and resignify its affective bonds.